Case report: Osimertinib administration during pregnancy in a woman with advanced EGFR-mutant non-small cell lung cancer - Soberanis Pina, Pamela; Lara-Mejía, Luis; Matias-Cruz, Venecia; Barrón, Feliciano; Cardona, Andrés F.; Raez, Luis E.; Rios-Garcia, Eduardo; Arrieta, Oscar (Frontiers in Oncology, 2023)
Lung cancer (LC) is one of the most common causes of death worldwide. The identification of oncogene-addicted driving mutations suitable for targeted therapy has improved clinical outcomes in advanced diseases. Clinical trials, on the other hand, rarely involve vulnerable groups such as pregnant women. We report a 37-year-old woman with advanced non-small cell lung cancer (NSCLC) harboring an exon 19 deletion of EGFR treated with afatinib. After the initial treatment, the patient achieved a complete response and had an unplanned pregnancy. Targeted therapy was withheld during the first trimester and resumed with osimertinib in the second trimester in which the patient developed oligohydramnios and intrauterine growth restriction (IUGR) of the baby. Osimertinib was delayed at two different times during the third trimester with complete resolution of the oligohydramnios. The baby was born at 37.3 weeks of gestation (WOG) with no signs of congenital disorders. After delivery, the mother restarted osimertinib and maintained a complete response. This case suggests that osimertinib could be an acceptable option for tumor control during pregnancy in EGFR-mutant NSCLC. This information do not replace current recommendations for avoiding pregnancy and promoting contraceptive usage in patients receiving any cancer therapy.